Detection and molecular characterization of hepatitis E virus in clinical, environmental and putative animal sources - Ishida, Setsuko; Yoshizumi, Shima; Ikeda, Tetsuya; Miyoshi, Masahiro; Goto, Akiko; Matsubayashi, Keiji; Ikeda, Hisami (Archives of virology, 2012)
Putative animal reservoirs and environmental samples were studied to investigate potential routes of transmission for indigenous hepatitis E virus (HEV) infection in Hokkaido, Japan. A total of 468 liver samples and 954 environmental samples were collected from 2003 to 2011 for this study. Four swine livers (1 %) were positive for HEV RNA; two strains belonged to genotype 3 and the other two strains were genotype 4. Genotype 3 HEV was detected in a sewage sample and a seawater sample. HEV strains derived from swine liver, seawater and raw sewage samples shared 93-100 % sequence similarity with human HEV strains.